2019
DOI: 10.3390/jof6010010
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gene Dosage and Heterozygosity on the Diploid Pathobiont Candida albicans

Abstract: Candida albicans is a fungal species that can colonize multiple niches in the human host where it can grow either as a commensal or as an opportunistic pathogen. The genome of C. albicans has long been of considerable interest, given that it is highly plastic and can undergo a wide variety of alterations. These changes play a fundamental role in determining C. albicans traits and have been shown to enable adaptation both to the host and to antifungal drugs. C. albicans isolates contain a heterozygous diploid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 134 publications
0
19
0
Order By: Relevance
“…Tetraploid genome reduction generates massive karyotypic heterogeneity in cell populations through its parasexual cycle (22,23) by reassorting chromosomes into new allelic combinations, which has been proposed to facilitate rapid adaptation (15). Others have demonstrated that decreased heterozygosity correlates with decreased in pathogen fitness and virulence (29,39,51). In our study, we measured genome size changes but have not yet characterized the allelic composition in our host-derived isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Tetraploid genome reduction generates massive karyotypic heterogeneity in cell populations through its parasexual cycle (22,23) by reassorting chromosomes into new allelic combinations, which has been proposed to facilitate rapid adaptation (15). Others have demonstrated that decreased heterozygosity correlates with decreased in pathogen fitness and virulence (29,39,51). In our study, we measured genome size changes but have not yet characterized the allelic composition in our host-derived isolates.…”
Section: Discussionmentioning
confidence: 99%
“… 2014 ; Tso et al . 2018 ; Liang and Bennett 2019 ) as well as resistance to antifungal therapy (Coste et al . 2006 ; Ford et al .…”
Section: The Fungusmentioning
confidence: 99%
“…A parasexual cycle commonly leads to aneuploid forms, when the yeast cells acquire an extra chromosomal information, leading to an increased copy number of genes. Aneuploidy may be induced by stress conditions (UV exposure, antifungal drugs) [ 47 , 48 ]. Changes may be produced by different growth conditions, for example, in vivo exposure of Candida inducing highly variable isolates as compared to its in vitro exposure [ 30 ].…”
Section: The Virulence Of Candida Sppmentioning
confidence: 99%
“…This does not necessarily mean that heterozygous genes are non-functional, as many genes that present SNPs that encode stop codons are actually functional. LoH could reflect resistance to fluconazole or phenotypic changes (grey colonies with a lower chance of being phagocytized by macrophages and neutrophils and better fitness for colonizing the host) [ 47 , 49 ]. The LoH rate is variable and increases under the stress of external factors such as antifungal drugs or increased temperature [ 30 ].…”
Section: The Virulence Of Candida Sppmentioning
confidence: 99%